Determinants of Disease Outcome following Helicobacter pylori Infection in Children - Nicola L Jones; Andrew S Day; Philip M Sherman (Canadian Journal of Gastroenterology)
Helicobacter pylori infection is primarily acquired during childhood, causes chronic, active gastritis and peptic ulcer disease, and is associated with the development of gastric malignancies. However, only a small number of infected individuals ever develop the more severe sequelae of peptic ulcer disease and gastric cancers. Therefore, the identification of bacterial and host factors that play a role in determining the outcomes and pathophysiology of infection is a major focus of current research. Recent advances in the understanding of disease pathogenesis are critically considered, with particular reference to the paediatric population.